Report on Indian and State Administrative Services and Problems of District Administration - Planning Commission (Planning Commission, 1962)
As soon as I began work, I wrote letters to Chief Ministers of States (on December 13, 1960) setting out the specific problems on which information was needed and requesting their advice and assistance in the studies I was undertaking. Replies to this were received from Chief Ministers in the course of 1961. Early in 1961, the Home Ministry reviewed the position in regard to the strength of the I.A.S. cadre in the light of the replies from Chief Ministers so far received and of information available with them and prepared a memorandum. This memorandum was sent to States for their comments.
Government of India Planning Commission
Government of India Planning Commission